Quantitative Structure-Activity Relationships of Thiazole Amide Derivatives Containing 2-Substituted-1,3-thiazolidine Ring - Chai, Xing-Quan; Bi, Hui-Min; Dong, Chun-Hua (Asian Journal of Chemistry, 2015)
The quantum correlation between antibacterial activity of thiazole amide derivatives containing 2-substituted-1,3-thiazolidine ring and structure were studied. The quantum study of these compounds was calculated by Gaussian 03 program. Then the related parameters were calculated and quantitative structure-activity relationships were studied. The study found that correlation is existed between the antibacterial activity of compounds and hydrophobic parameter (log P) and energy of LUMO orbital. The good parameters were selected for the linear regression. The result shows that linear equations was only related to log P. By analyzing of orbital composition, it was found that R(N) atoms were the active sites.